Integrasi Penerapan Sistem Manajemen ISO 9001 dan ISO 14001 pada Perusahaan Rekanan Pertamina - Baidhok, Wardatul; Prasetyono, Prasetyono (LPPM Institut Nasional Laa Roiba Bogor, 2024)
PT CMS is a company that operates in the service sector, namely, 3kg LPG gas cylinder retester or BPT (Cylinder Maintenance Workshop). The management system integrated at PT CMS includes the ISO 9001:2015 Quality Management System and ISO 14001:2015 Environmental Management System. The purpose of this research is to understand how the implementation of ISO 9001 and ISO 14001 standards affects the performance of the PT CMS company. The research method used in this article is a descriptive qualitative approach, where data is collected through interviews with the parties concerned. The data obtained is primary data resulting from the researcher's interviews with sources. The research results show that ISO standards have been implemented well, as shown by the results of the external audit report with a score of 94.12, where this score is included in the fair and positive category. The impact of the integration of the implementation of ISO 9001 and ISO 14001 at PT CMS is, ensuring the company's quality and environment, increasing the trust of the service provider (Pertamina), increasing the tube maintenance quota, can improve the company's quality without damaging the surrounding environment.